Bridges between Russia and Italy: Studies in Byzantine Art at the Beginning of the 20th century - Gasbarri, Giovanni (Actual Problems of Theory and History of Art, 2025)
This paper aims to emphasize, in particular, the important role played by Russian studies in helping Italian scholars to rediscover the arts and culture of Byzantium. In this context, the cultural relationships with Russia emerge as one of the most relevant boosts for improving byzantine studies in Italy. Despite the difficulties in reading texts in a language that was largely unknown in Western Europe, studies by Russian scholars concerning the arts and culture of Byzantium were increasingly quoted and mentioned in Italian researches.